2013
DOI: 10.1186/1476-0711-12-25
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum procalcitonin levels in pregnant patients with asymptomatic bacteriuria

Abstract: BackgroundAmong the pregnancy urinary tract infections, asymptomatic bacteriuria (ASB) is the most common one. Untreated ASB can progress to pyelonephritis in 30-50% of the patients and can also result in prematurity in 27% of the pregnancy so it needs immediate diagnosis and treatment. In this study, we wanted to evaluate procalcitonin levels, compared to other inflammatory in pregnant women with ASB.MethodsThe study was designed between the period of January 2012 and February 2013 at Sakarya University Schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
5
13
0
1
Order By: Relevance
“…The most affected maternal age range was between 25 and 29 years as observed by other authors [3,14]. ASB was rarely found among teenagers [3], as in our series.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The most affected maternal age range was between 25 and 29 years as observed by other authors [3,14]. ASB was rarely found among teenagers [3], as in our series.…”
Section: Discussionsupporting
confidence: 84%
“…Our prevalence of ASB (7.8%) is within the range found worldwide which varies between 2 and 11% [13,14]. This might show that the prevalence of ASB is less influenced by the country income status.…”
Section: Discussionsupporting
confidence: 75%
“…Ebrahimi, Maltepe, and Einarson (2010) indicated that ginger was used in the complementary treatment of hyperemesis gravidarum. Ginger has an antiemetic effect in hyperemesis gravidarum and postoperative nausea and/or vomiting (Bilir, Akdemir, Ozden, Cevrioglu, & Bilir, 2013;Hines, Steels, Chang, & Gibbons, 2012;Marcus & Snodgrass, 2005). However, these studies were rather limited in how ginger may affect CINV (Alparslan et al, 2012;Chrubasik, Pittler, & Roufogalis, 2005).…”
mentioning
confidence: 99%
“…Ieškodami žymenų, kurie padėtų numatyti ŠTI pasikartojimo riziką, Filiz Bilir su kolegomis 2013 m. paskelbė tyrimą, kuriame pirmą kartą buvo tirtas proklacitonino panaudojimas nėščiųjų besimptomės bakteriurijos diagnostikoje [35]. Tyrime pastebėta, kad: 1. prokalcitonino koncentracija kraujo serume buvo statistiškai patikimai didesnė tarp sergančiųjų besimptome bakteriurija nei tarp sveikų nėščiųjų; 2. didelė prokalcitonino koncentracija pirmą kartą diagnozuojama besimptomės bakteriurijos metu gali įspėti apie ŠTI pasikartojimą ateityje; 3. sveikų nėščių moterų kraujo serume prokalcitonino lygis buvo normalus, tuo tarpu eritrocitų nusėdimo greičio, C reaktyvaus baltymo koncentracijos ir leukocitų skaičius buvo gerokai padidėję.…”
Section: įVadasunclassified